'Make it Stick' -Influence of Hydrophobicity of Nano Silica Functionalization on Dispersion and Breakdown Performance in BOPP Nanocomposites - Werner, Siegfried; Kellner, Michael; Kaschta, Joachim; Schubert, Dirk W. (Proceedings of the 2024 IEEE 5th International Conference on Dielectrics, ICD 2024, 2024)
This paper aims to evaluate commercial silica nanoparticles with surface functionalization of different hydrophobicity for BOPP capacitor films using a small-scale production process requiring only a few grams of particles. Therefore, capacitor grade PP and 0.5 wt.% of fumed silica were compounded in a laboratory mixer, hot pressed into plugs and biaxially oriented on a laboratory stretching device. Three commercial particle systems with comparable specific surface area but different surface functionalization (methacrylate silane (MAS), octamethylcyclotetrasiloxane (OMCTS) or dimethyldichlorosilane (DDS)) as well as unfunctionalized silica were investigated. Optical microscopy and scanning electron microscopy showed that dispersion improved greatly with higher hydrophobicity. Interestingly, short-term dielectric strength for OMCTS functionalization was 37 V/μm higher than for the PP reference and 34 V/μm higher than for DDS, although both consisted of the same chemical groups. Long-term voltage endurance was improved for the polar MAS functionalization despite the short-term performance being governed by agglomerates. Therefore, a combination of hydrophobic and hydrophilic groups seems promising.
CRIS-Team Scopus Importer:2024-09-06
Keywords: BOPP; dielectric strength; dispersion; nanocomposite; surface functionalization; voltage endurance